Perencanaan Sistem Penerangan Ruangan - Soetjipto Soewono; Evi Suhaevi (Sekolah Tinggi Teknik PLN, 2019)
Lighting becomes one of the important factors to support facilities for teaching and learning study. STT PLN building is one of the buildings use as classroom for teaching and learning study that will improve the quality of facilities. Standar lighting in the class room 250 lux base on SNI 03-6197-2000.Research was conducted in the STT PLN building which was used as a class room. Activities include measuring ligh in class room, measuring the width, height and length of s room by using a meter to determine the distance between armatures in the calss room. The existence of this research is expected to be a solution for class building to Standar National Indonesian (SNI). Keywords: storing light, calss room, standar